Preparation method of composition, loudspeaker sound-absorbing material and manufacturing method of loudspeaker sound-absorbing material
By preparing a three-dimensional network structure in which porous materials and reinforced fibers are interwoven, the problem that granular acoustic materials are easily broken under high-frequency vibration is solved, and the mechanical strength and acoustic performance of speaker sound-absorbing materials are improved.
Patent Information
- Application Number
- CN202411400855.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-21
AI Technical Summary
Existing particle acoustic materials are prone to breaking due to high-frequency vibration when the speaker is working, resulting in damage to the speaker and affecting the hearing.
The composition is prepared by mixing porous materials, binders, low-shrinkage additives and water. Through extrusion, shearing and roasting processes, strip-shaped or rod-shaped products are obtained, and interwoven with reinforcing fibers to form a three-dimensional network structure.
It improves the mechanical strength of the speaker's sound-absorbing material to prevent breakage, and reduces the resistance of the sound film through the adsorption and desorption capabilities of the three-dimensional structure to improve the acoustic performance.
Smart Images

Figure CN119330633A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of material manufacturing, and in particular relates to a preparation method of a composition and a speaker sound-absorbing material and a manufacturing method. Background Art
[0002] With the continuous development of electronic products such as mobile terminal devices, laptops, tablets, AR and VR, users have higher and higher requirements for audio quality. The low-frequency performance, bandwidth and sound flatness of micro speakers seriously affect the user's experience of sound quality details.
[0003] At present, the acoustic materials of micro speakers are generally granular microsphere products with a diameter of 100 to 600 μm. They are mostly made of mesoporous materials with a few nanometers as raw materials and are made by gluing and drying. The interior of the granular microsphere products has characteristic micron-level open channels, which can significantly reduce the resonant frequency by more than 100 Hz and increase the sound by 5 dB. In terms of improving the performance of micro speakers, the more microspheres are used, the smaller the volume of the speaker, and the greater the virtual increase coefficient. However, during the application of granular acoustic materials, when the speaker is working, the gas vibration in the shell driven by the voice coil may cause the filled granular acoustic material to vibrate at a high frequency in the cavity, and collisions occur between particles and between particles and the cavity wall, which not only affects the listening experience, but even the powder that falls off when the particles are broken may spread through the mesh to the inside of the speaker and damage the speaker unit.
[0004] Therefore, it has become an urgent problem for technical personnel in this field to develop a preparation method of a composition and a speaker sound-absorbing material and a manufacturing method to solve the technical defects in the prior art that granular acoustic materials affect the listening experience and are prone to damage the speaker unit when the particles are broken. Summary of the invention
[0005] Based on this, it is necessary to provide a method for preparing a composition and a speaker sound-absorbing material and manufacturing method to address the technical defects of existing technologies, such as the granular acoustic materials that affect the listening experience and the easy damage to the speaker unit when the particles are broken.
[0006] The present application provides a method for preparing a composition, the preparation method comprising: mixing a porous material, a binder, a low shrinkage additive and water to obtain a mixed slurry, and then extruding the mixed slurry, shearing and baking to obtain a strip and / or rod-shaped product.
[0007] In one embodiment, the raw materials of the composition include: porous material, binder, low shrinkage additive and water;
[0008] The porous material is selected from any one or more of zeolite molecular sieve, activated carbon, calcium carbonate, hydrogel or aerogel.
[0009] In one embodiment, the raw materials of the composition include, by weight: 15 to 62 parts of porous material, 15 to 37 parts of binder, 3 to 8 parts of low shrinkage additive and 15 to 40 parts of water.
[0010] In one embodiment, the low shrinkage additive is selected from any one or more of polyvinyl acetate, polymethyl methacrylate, polystyrene, thermoplastic polyurethane and polyester.
[0011] In one embodiment, the binder is selected from any one or more of polyvinyl alcohol, polyurethane, polyacrylate, epoxy acrylate, polyether acrylate and amino acrylate.
[0012] In one embodiment, the raw materials of the composition further include: a release agent, and the release agent accounts for 0.5 to 4 parts of the composition.
[0013] In one embodiment, the release agent is selected from any one or more of silicone oil, polyethylene glycol, microcrystalline wax and mica.
[0014] In one embodiment, the length of the product is 3 to 10 mm, and the diameter of the product is 7 to 12 μm.
[0015] In one embodiment, the length of the product is 5 to 10 mm.
[0016] In one of the embodiments, the sintering temperature is 200° C. to 650° C., and the sintering time is 0.5 to 5 hours.
[0017] In one of the embodiments, the sintering temperature is 280° C. to 550° C., and the sintering time is 1 to 2.5 hours.
[0018] The present application also provides a loudspeaker sound-absorbing material, the loudspeaker sound-absorbing material comprising: a product obtained by any one of the preparation methods described above and reinforcing fibers, wherein the composition or product is interwoven with the reinforcing fibers to form a three-dimensional network structure;
[0019] The mass ratio of the composition or product to the reinforcing fiber is (30-95):(5-70).
[0020] In one embodiment, the diameter of a single reinforcing fiber is 2 to 30 μm, and the length of a single reinforcing fiber is 3 to 12 mm.
[0021] In one embodiment, the diameter of a single reinforcing fiber is 3-20 μm, and the length of a single reinforcing fiber is 5-10 mm.
[0022] In one embodiment, the diameter of a single reinforcing fiber is 5 to 12 μm, and the length of a single reinforcing fiber is 3 to 12 mm.
[0023] The present application also provides a method for manufacturing a loudspeaker sound-absorbing material comprising any one of the above items, the manufacturing method comprising:
[0024] Step 1: The composition and / or product and the reinforcing fiber are dispersed and decomposed separately to obtain a first product;
[0025] Step 2, the first product is dehydrated and paper-formed to obtain a sheet-like second product;
[0026] Step 3: The second product is subjected to heat pressing to obtain a loudspeaker sound-absorbing material.
[0027] In one embodiment, the weight of the speaker sound absorbing material is 100-800 g / m 2 The thickness of the loudspeaker sound-absorbing material is 0.5 to 2.5 mm.
[0028] In one embodiment, the weight of the speaker sound absorbing material is 200-600 g / m 2 The thickness of the loudspeaker sound-absorbing material is 0.8 to 2.2 mm.
[0029] In one embodiment, in step three, the temperature of the hot pressing is 150-300° C., and the time of the hot pressing is 3-15 minutes.
[0030] In summary, the present application provides a method for preparing a composition, which is: a porous material, a binder, a low shrinkage additive and water are mixed to obtain a mixed slurry, and the mixed slurry is extruded, sheared and baked to obtain a strip and / or rod-shaped product. The present application also provides a speaker sound-absorbing material and a method for manufacturing the same. In the technical solution provided by the present application, the porous material is a three-dimensional structure formed by polyhedral holes gathered in space, which has good mechanical strength and is not easy to break after being vibrated; at the same time, during high-frequency vibration, the three-dimensional structure can adsorb and desorb sound, reduce the resistance of the sound membrane, further reduce the resonant frequency F0, and effectively improve the acoustic performance. By selecting a specific porous material, the technical defects of the prior art that granular acoustic materials affect the listening experience and are prone to damage the speaker unit when the particles are broken are solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0032] Figure 1 A schematic flow chart of a method for manufacturing a loudspeaker sound-absorbing material in the technical solution provided in an embodiment of the present application. DETAILED DESCRIPTION
[0033] The embodiments of the present application provide a composition, a preparation method, a speaker sound-absorbing material, and a manufacturing method, which are used to solve the technical defects in the prior art that granular acoustic materials affect the listening experience and are prone to damage the speaker unit when the particles are broken.
[0034] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0035] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0037] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0038] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0039] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.
[0040] The present application provides a method for preparing a composition, which comprises: mixing a porous material, a binder, a low shrinkage additive and water to obtain a mixed slurry, extruding the mixed slurry and then baking it to obtain a strip and / or rod-shaped product.
[0041] In the preparation method provided in the present application, the raw materials of the composition include: porous material, binder, low shrinkage additive and water; the porous material is selected from: any one or more of zeolite molecular sieve, activated carbon, calcium carbonate, hydrogel or aerogel.
[0042] In the preparation method provided in the present application, the porous material can form a three-dimensional structure by agglomerating polyhedral holes in space, which has good mechanical strength and is not easy to break after being vibrated; at the same time, during high-frequency vibration, the three-dimensional structure can adsorb and desorb sound, reduce the resistance of the sound membrane, further reduce the resonance frequency F0, and effectively improve the acoustic performance.
[0043] At the same time, adding a low shrinkage additive to the raw materials of the composition can avoid the problem of warping and cracking of the product caused by volume compression and heat release during the curing process in the subsequent preparation process of the composition, ensuring that the prepared product can achieve a high surface flatness and finish. By adding a low shrinkage additive to the raw materials of the composition, various defects that may be caused by thermal shrinkage in the preparation process can be effectively reduced, such as: warping deformation, surface ripples, local cracks, micro-glass fiber cotton fiber traces, surface matte, dimensional instability, etc.
[0044] To further optimize the technical solution, the raw materials of the composition include, by weight: 15 to 62 parts of porous material, 15 to 37 parts of binder, 3 to 8 parts of low shrinkage additive, 15 to 40 parts of water and 0.5 to 4 parts of release agent.
[0045] To further optimize the technical solution, while ensuring that the surface flatness and smoothness of the product can meet the requirements after the low-shrinkage additive is added, the low-shrinkage additive can be integrated with other raw material components in the composition. In the technical solution provided in the embodiment of the present application, the low-shrinkage additive is selected from any one or more of polyvinyl acetate, polymethyl methacrylate, polystyrene, thermoplastic polyurethane and polyester.
[0046] The binder can promote the effective fusion of the components in the raw materials of the composition, and plays an important role in improving the strength of the final product. In the technical scheme provided in the embodiment of the present application, the binder is selected from: any one or more of polyvinyl alcohol, polyurethane, polyurethane acrylate, polyacrylate, epoxy acrylate, polyether acrylate and amino acrylate.
[0047] To further optimize the technical solution, in the preparation method provided in the embodiment of the present application, the raw materials of the composition also include: a release agent, and the release agent accounts for 0.5 to 4 parts of the composition. By adding a small amount of release agent to the composition, the effect of the demoulding process in the subsequent preparation process of the composition can be improved, which has a good promoting effect on improving product quality. At the same time, considering that adding too much release agent may affect the strength of the final product and cause the surface of the product to be rough, according to the raw material formula and ratio of the composition in the embodiment of the present application, the amount of release agent added accounts for 0.5 to 4 parts of the composition.
[0048] To further optimize the technical solution, taking into account the good demoulding effect of the demoulding agent and the fact that the addition of the demoulding agent does not cause significant adverse effects on the appearance and strength of the final product, in the technical solution provided in the embodiment of the present application, the demoulding agent is selected from: any one or more of silicone oil, polyethylene glycol, microcrystalline wax and mica.
[0049] The preparation method of the composition is simple and convenient, and can realize large-scale continuous production; in particular, in the extrusion process of the preparation method, extremely fine single-screw extrusion can be selected, and the strip-shaped and / or rod-shaped products obtained have high dimensional consistency and can be precisely controlled in size, and have better dimensional consistency than spherical particles prepared in the prior art.
[0050] At the same time, the extrusion process is adopted in the preparation method. Under the action of external force during the extrusion molding process, the structure of the porous material is reorganized and distributed, the gap between the porous materials becomes smaller, and the interface between adjacent porous materials is fused, which further improves the mechanical strength and can effectively prevent collapse during the subsequent roasting process.
[0051] Since the product is in the shape of a strip and / or a rod, when the product is applied to the rear cavity of a speaker, the rear cavity space of the speaker can be effectively utilized, thereby improving the space utilization rate of the rear cavity of the speaker. It can also solve the problem of powdering during the application of the speaker product, thereby avoiding the risk of speaker contamination.
[0052] To further optimize the technical solution and the space utilization of the manufactured product, in the technical solution provided in the embodiment of the present application, the length of the product is 3 to 15 mm, and the diameter of the product is in the micron level.
[0053] By further optimizing the technical solution, the length of the product is 5 to 10 mm, and the diameter of the product is 7 to 12 μm.
[0054] In order to effectively improve the strength of the product obtained by the preparation method and improve the quality stability of the product, in the preparation method provided in the embodiment of the present application, the sintering temperature of the calcination is 200°C to 650°C, and the sintering time of the calcination is 0.5 to 5h.
[0055] To further optimize the technical solution, the sintering temperature is 280°C to 550°C, and the sintering time is 1 to 2.5 hours.
[0056] The present application also provides a loudspeaker sound-absorbing material, comprising: the above-mentioned composition or the product obtained by the above-mentioned preparation method and reinforcing fibers, wherein the composition or the product and the reinforcing fibers are interwoven to form a three-dimensional network structure; the mass ratio of the composition or the product to the reinforcing fibers is (30-95):(5-70).
[0057] In the loudspeaker sound-absorbing material provided in the embodiment of the present application, the composition or product is interwoven with the reinforcing fibers to form a three-dimensional network structure, forming a composite interwoven structure in the transverse and longitudinal directions. When the loudspeaker sound diaphragm vibrates at a high frequency, the loudspeaker sound-absorbing material block can absorb and desorb sound through the strip / rod-shaped sound-absorbing material with a three-dimensional network structure, which can effectively reduce the resistance of the sound diaphragm and form a virtual effect similar to physically increasing the rear cavity of the loudspeaker, thereby effectively reducing the resonant frequency F0 and significantly increasing the acoustic performance, especially the low-frequency performance. At the same time, the use of reinforcing fibers can further enhance the mechanical properties of the loudspeaker sound-absorbing material block, effectively improving the problem of vibration and crushing pollution of the loudspeaker caused by directly filling the sound-absorbing balls, thereby extending the service life of the loudspeaker.
[0058] In the actual application process, the reinforcing fibers in the speaker sound-absorbing materials here should try to avoid using natural fibers such as cotton fibers, linen fibers, etc. This is because natural fibers have many tiny gaps and capillaries in their structure, which causes the fibers themselves to have certain hygroscopicity and regain. When natural fibers are used to prepare speaker sound-absorbing materials, since the speakers are usually used in scenes exposed to the air, it is difficult to avoid the natural fibers absorbing moisture in the air, resulting in poor speaker sound quality, noise or abnormal sound, which seriously affects the product experience.
[0059] More specifically, the reinforcing fiber may be any one or more of polypropylene fiber, PET bonding fiber, nylon fiber, and polyvinyl alcohol fiber.
[0060] In actual application, the speaker sound-absorbing material can be a single-layer reinforced fiber-single-layer composition / product, a composite superposition of two layers of reinforced fiber-single-layer composition / product, or a "sandwich" structure of a single-layer reinforced fiber-single-layer composition / product-single-layer reinforced fiber.
[0061] The size of the speaker sound-absorbing material can be cut at will, and it has a wide range of applicability. When used in micro speakers, it can improve the low-frequency characteristics of the speaker, giving users a better acoustic experience and low-frequency impact. Furthermore, since the speaker sound-absorbing material saves more space, the utilization rate of the rear cavity space is improved. Correspondingly, the volume of the rear sound cavity increases, and the amplitude of its diaphragm will also increase, which means that the speaker can bring greater loudness, allowing users to experience high-loudness sound.
[0062] To further optimize the technical solution, in order to achieve better molding during wet papermaking and increase the uniformity of the material, in the technical solution provided in the embodiment of the present application, the diameter of a single reinforcing fiber is 2 to 30 μm, and the length of a single reinforcing fiber is 3 to 12 mm.
[0063] To further optimize the technical solution, the diameter of a single reinforcing fiber is 3 to 20 μm, and the length of a single reinforcing fiber is 5 to 10 mm.
[0064] To further optimize the technical solution, the diameter of a single reinforcing fiber is 5 to 12 μm, and the length of a single reinforcing fiber is 3 to 12 mm.
[0065] See here Figure 1 The present application also provides a method for manufacturing the above-mentioned loudspeaker sound-absorbing material. Figure 1 The present invention is a schematic flow chart of a method for manufacturing a loudspeaker sound-absorbing material.
[0066] Step 1: The composition and / or product and the reinforcing fiber are dispersed and decomposed separately to obtain a first product;
[0067] Step 2, the first product is dehydrated and paper-formed to obtain a sheet-like second product;
[0068] Step 3: The second product is subjected to heat pressing to obtain a loudspeaker sound-absorbing material.
[0069] The composition and / or product is mixed with the reinforcing fiber and the ratio of the composition and / or product to the reinforcing fiber is effectively adjusted to obtain a loudspeaker sound-absorbing material with good mechanical properties and capable of improving the low-frequency performance of the loudspeaker.
[0070] To further optimize the technical solution, in order to better match the needs of different satellite speakers, the weight of the speaker sound-absorbing material is 100-800g / m 2 , the thickness of the speaker sound-absorbing material is 0.5 to 2.5 mm.
[0071] To further optimize the technical solution, the weight of the speaker sound-absorbing material is 200-600g / m 2 , the thickness of the speaker sound-absorbing material is 0.8 to 2.2 mm.
[0072] Taking into account both the good mechanical properties of the speaker sound-absorbing material and reducing the energy consumption of hot pressing, in the technical solution provided in the embodiment of the present application, in step three, the hot pressing temperature is 150-300° C., and the hot pressing time is 3-15 minutes.
[0073] The following combination Figure 1 , and carry out the specific preparation of the loudspeaker sound-absorbing material.
[0074] Example 1
[0075] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 200 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0076] Among them, the reinforcing fibers are composed of water-dispersible chemical synthetic fibers and thermal bonding fibers. The water-dispersible chemical synthetic fibers are a combination of polyester fibers, micro-glass fiber cotton fibers and aramid fibers, with an absolute dry mass accounting for 40%; the thermal bonding fibers are PET bonding fibers, with an absolute dry mass accounting for 60%.
[0077] The porous material is MFI zeolite molecular sieve, and its average particle size is 500nm, including micropores with a pore size of 0.50nm and mesopores with a pore size of 10nm. The release agent is silicone oil, the binder is polyurethane, and the low shrinkage additive is polyvinyl acetate.
[0078] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 70.00%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 30.00%.
[0079] The manufacturing method of the speaker sound absorbing material is as follows:
[0080] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0081] The preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 60%:15%:19%:5.5%:0.5%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a strip and / or rod-shaped sound-absorbing material precursor with a length of 3mm and a diameter of 7μm is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is calcined at 400°C for 2h to obtain a strip and / or rod-shaped sound-absorbing material.
[0082] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0083] Step 3: Dry the sheet material obtained in step 2 at 105° C., and hot-press at 160° C. and 1 MPa for 5 min to obtain a composite sound-absorbing material block for a speaker.
[0084] Example 2
[0085] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 450 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0086] The reinforcing fibers are composed of water-dispersible chemical synthetic fibers and thermal bonding fibers, wherein the water-dispersible chemical synthetic fibers are a combination of micro-glass wool fibers, quartz micro-glass wool fibers and ceramic fibers, with an absolute dry mass accounting for 50%; the thermal bonding fibers are nylon fibers, with an absolute dry mass accounting for 50%;
[0087] The porous material is activated carbon, and its average particle size is 300nm, including micropores with a pore size of 0.43nm and mesopores with a pore size of 11nm. The release agent is polyethylene glycol, the binder is polyvinyl alcohol, and the low shrinkage additive is polymethyl methacrylate.
[0088] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 45.00%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 55.00%.
[0089] The manufacturing method of the speaker sound absorbing material is as follows:
[0090] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0091] Among them, the preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 45%:22%:23%:8%:2%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a strip and / or rod-shaped sound-absorbing material with a length of 5mm and a diameter of 8μm is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material precursor is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is roasted at 550°C for 1h to obtain a strip and / or rod-shaped sound-absorbing material.
[0092] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0093] Step 3: Dry the sheet material obtained in step 2 at 110° C., and hot-press at 170° C. and 1 MPa for 8 min to obtain a composite sound-absorbing material block for a speaker.
[0094] Example 3
[0095] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 660 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0096] Among them, the reinforcing fiber is composed of water-dispersible chemical synthetic fiber and thermal bonding fiber, wherein the water-dispersible chemical synthetic fiber is a combination of nylon fiber, quartz micro-glass fiber and metal fiber, and the absolute dry weight accounts for 20%; the thermal bonding fiber is polypropylene fiber, and the absolute dry weight accounts for 80%;
[0097] The porous material is silicon dioxide aerogel, the average particle size of which is 50nm, including mesopores with a pore size of 5-10nm. The mold release agent is polycrystalline wax, the binder is polyacrylate, and the low shrinkage additive is polystyrene.
[0098] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 24.00%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 76.00%.
[0099] The manufacturing method of the speaker sound absorbing material is as follows:
[0100] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0101] Among them, the preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 50%:30%:14%:3%:3%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a strip and / or rod-shaped sound-absorbing material precursor with a length of 7mm and a diameter of 10μm is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is calcined at 280°C for 2.5h to obtain a strip and / or rod-shaped sound-absorbing material.
[0102] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0103] Step 3: Dry the sheet material obtained in step 2 at 120° C., and hot-press at 150° C. and 1 MPa for 12 minutes to obtain a composite sound-absorbing material block for a speaker.
[0104] Example 4
[0105] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 800 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0106] Among them, the reinforcing fiber is composed of water-dispersible chemical synthetic fiber and thermal bonding fiber, wherein the water-dispersible chemical synthetic fiber is a combination of polyester fiber, ceramic fiber and polyester fiber, and the absolute dry weight accounts for 30.00%; the thermal bonding fiber is PET bonding fiber, and the absolute dry weight accounts for 70.00%;
[0107] The porous material is surface porous calcium carbonate, the average particle size of which is 600nm, including micropores with a pore size of 0.59nm and mesopores with a pore size of 25nm. The mold release agent is mica, the binder is epoxy acrylate, and the low shrinkage additive is thermoplastic polyurethane.
[0108] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 10.00%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 90.00%.
[0109] The manufacturing method of the speaker sound absorbing material is as follows:
[0110] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0111] Among them, the preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 28%:28%:34%:6%:4%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a 9mm and 10μm diameter strip and / or rod-shaped sound-absorbing material precursor is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is calcined at 330°C for 2h to obtain a strip and / or rod-shaped sound-absorbing material.
[0112] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0113] Step 3: Dry the sheet material obtained in step 2 at 120° C., and hot-press at 300° C. and 1 MPa for 3 min to obtain a composite sound-absorbing material block for a speaker.
[0114] Example 5
[0115] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 300 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0116] Among them, the reinforcing fiber is composed of water-dispersible chemical synthetic fiber and thermal bonding fiber, wherein the water-dispersible chemical synthetic fiber is a combination of nylon fiber, quartz micro-glass fiber and metal fiber, and the absolute dry weight accounts for 65%; the thermal bonding fiber is polypropylene fiber, and the absolute dry weight accounts for 35%;
[0117] The porous material is a hydrogel with an average particle size of 50 nm, including mesopores with a pore size of 5 to 10 nm. The mold release agent is silicone oil, the binder is polyether acrylate, and the low shrinkage additive is polyester.
[0118] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 50%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 50%.
[0119] The manufacturing method of the speaker sound absorbing material is as follows:
[0120] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0121] Among them, the preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 48%:31%:15%:4%:2%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a 10mm, 12μm diameter strip and / or rod-shaped sound-absorbing material precursor is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is calcined at 270°C for 2.5h to obtain a strip and / or rod-shaped sound-absorbing material.
[0122] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0123] Step 3: Dry the sheet material obtained in step 2 at 115° C., and hot-press at 200° C. and 1 MPa for 9 minutes to obtain a composite sound-absorbing material block for a speaker.
[0124] Comparative Example 1
[0125] This embodiment is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this embodiment, the weight of the loudspeaker sound-absorbing material is 450 g / m 2 , which is formed by interweaving reinforcing fibers and strip / rod-shaped sound-absorbing materials, and the sound-absorbing composite material block has a three-dimensional network structure inside.
[0126] The reinforcing fibers are composed of water-dispersible chemical synthetic fibers and thermal bonding fibers, wherein the water-dispersible chemical synthetic fibers are a combination of micro-glass wool fibers, quartz micro-glass wool fibers and ceramic fibers, with an absolute dry mass accounting for 50%; the thermal bonding fibers are nylon fibers, with an absolute dry mass accounting for 50%;
[0127] The porous material is activated carbon, and its average particle size is 300nm, including micropores with a pore size of 0.43nm and mesopores with a pore size of 11nm. The release agent is polyethylene glycol, the binder is polyvinyl alcohol, and the low shrinkage additive is polymethyl methacrylate.
[0128] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 45.00%, and the absolute dry mass of the strip / rod-shaped sound-absorbing material accounts for 55.00%.
[0129] The manufacturing method of the speaker sound absorbing material is as follows:
[0130] Step 1: Dispersing the reinforcing fiber and the porous sound-absorbing material in water according to the above formula to obtain a reinforcing fiber suspension and a porous sound-absorbing material dispersion;
[0131] Among them, the preparation method of the porous sound-absorbing material is as follows: the porous material, the binder, water, the low shrinkage additive and the release agent are uniformly mixed in a mass ratio of 45%:22%:23%:8%:2%, and compounded into a mixed slurry with certain fluidity and viscosity, and the obtained mixed slurry is put into a single screw extruder with a micron-level extrusion gap, and a 10mm, 12μm diameter strip and / or rod-shaped sound-absorbing material is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material precursor is obtained by adjusting the process parameters. The strip and / or rod-shaped sound-absorbing material is roasted at 550°C for 1h to obtain a strip and / or rod-shaped sound-absorbing material.
[0132] Step 2: Under the condition of mechanical stirring, the reinforcing fiber suspension and the porous sound-absorbing material dispersion are successively added into a sheet making machine, mixed evenly, and then dehydrated and filtered to obtain a sheet material;
[0133] Step 3: Dry the sheet material obtained in step 2 at 110° C., and hot-press at 170° C. and 1 MPa for 8 min to obtain a composite sound-absorbing material block for a speaker.
[0134] Comparative Example 2
[0135] This comparative example is a specific embodiment of manufacturing a loudspeaker sound-absorbing material. In this comparative example, the weight of the loudspeaker sound-absorbing material prepared is 450g / m 2 , which is formed by interweaving reinforcing fibers and sound-absorbing particles, and the interior of the sound-absorbing composite material block has a cross-formed network structure.
[0136] The reinforcing fibers are composed of water-dispersible chemical synthetic fibers and thermal bonding fibers, wherein the water-dispersible chemical synthetic fibers are a combination of nylon fibers, quartz fibers and metal fibers, accounting for 65% of the absolute dry weight; the thermal bonding fibers are polypropylene fibers, accounting for 35% of the absolute dry weight;
[0137] The sound-absorbing material is conventional commercially available sound-absorbing particles, with an average particle size of 50 nm, including mesopores with a pore size of 5 to 10 nm. The mold release agent is silicone oil, the adhesive is polyether acrylate, and the low shrinkage additive is polyester.
[0138] Taking the total weight of the loudspeaker sound-absorbing material as 100%, the absolute dry mass of the reinforcing fiber accounts for 50%, and the absolute dry mass of the sound-absorbing particle material accounts for 50%.
[0139] The manufacturing method of the speaker sound absorbing material is as follows:
[0140] Step 1: Dispersing the reinforcing fiber and the sound-absorbing particle material in water according to the above formula to obtain a reinforcing fiber-sound-absorbing particle material dispersion;
[0141] Step 2: Dewatering and filtering the dispersion of the reinforcing fiber-sound-absorbing particle material to obtain a sheet-like sound-absorbing material;
[0142] Step 3: Dry the sheet material obtained in step 2 at 115° C., and hot-press at 200° C. and 1 MPa for 9 minutes to obtain a composite sound-absorbing material block for a speaker.
[0143] Example 6
[0144] The aerogel-zeolite sound-absorbing materials prepared in the above embodiments and comparative examples were cut into a size of 10*10 mm, and then the resonance frequency offset values of the sheet acoustic enhancement materials were tested respectively according to Section 7.4 of the group standard "Porous Sound-Absorbing Particles for Micro Speakers" (Standard No.: T / CECA 78-2022). The specific results are shown in Table 1 below.
[0145] The acoustic efficiency of the sheet acoustic enhancement material per unit mass is calculated according to the formula shown below, and the obtained acoustic efficiency data is shown in Table 1 below.
[0146] Acoustic efficiency = resonance frequency deviation value / (absolute dry mass of molecular sieve), unit: Hz / mg
[0147] Table 1: Summary of performance of loudspeaker sound absorbing materials 10*10mm in different embodiments
[0148]
[0149]
[0150] The acoustic enhancement particles filled in the speakers of commercially available electronic products were disassembled and tested, and the obtained experimental data are shown in Table 2.
[0151] Table 2: Acoustic performance and acoustic efficiency data of conventional commercially available acoustic enhancement particles
[0152] Mass(mg) △f0(Hz) Acoustic efficiency (Hz / mg) 6 7.8 1.300 15 18.1 1.207 50 56.5 1.108 72 80 1.111
[0153] By comparing the experimental data in Table 1 with the experimental data in Table 2, it can be seen that the loudspeaker sound-absorbing materials provided in Examples 1 to 5 of the present invention all have good acoustic properties, and the acoustic properties are better than those of conventional commercially available sound-absorbing particles.
[0154] By comparing the experimental data in Table 1 and Table 2, it can also be known that the acoustic performance of the loudspeaker sound-absorbing material provided in Example 2 is the same as that in Comparative Example 1, indicating that the reinforcing fibers selected in the present invention have little or no effect on the acoustic performance of the prepared sound-absorbing material. Compared with the loudspeaker sound-absorbing materials provided in Example 5 and Comparative Example 2, the absolute dry mass percentage of the sound-absorbing functional material is the same, both 50%, but the acoustic performance of Example 5 is better than that of Comparative Example 2. The reason is that the strip / rod-shaped sound-absorbing material and the reinforcing fibers in Example 5 have a high degree of disordered intersection, and the prepared loudspeaker sound-absorbing material has a higher void inside. The acoustic material prepared by acoustic enhancement particles and reinforcing fibers in Comparative Example 2 is very likely to cause uneven distribution of the two due to the density difference between the acoustic enhancement particles and the reinforcing fibers. After hot pressing, the thermal bonding fibers in the reinforcing fibers have a greater probability of forming a local low porosity area, thereby affecting the acoustic performance of the sound-absorbing material.
[0155] In summary, the present application provides a method for preparing a composition, which is: a porous material, a binder, a low shrinkage additive and water are mixed to obtain a mixed slurry, and the mixed slurry is extruded and then baked to obtain a strip and / or rod-shaped product. The present application also provides a speaker sound-absorbing material and a method for manufacturing the same. In the technical solution provided by the present application, the porous material is a three-dimensional structure formed by polyhedral holes gathered in space, which has good mechanical strength and is not easy to break after being vibrated; at the same time, during high-frequency vibration, the three-dimensional structure can adsorb and desorb sound, reduce the resistance of the sound membrane, further reduce the resonant frequency F0, and effectively improve the acoustic performance. By selecting a specific porous material, the technical defects of the prior art that granular acoustic materials affect the listening experience and are prone to damage the speaker unit when the particles are broken are solved.
[0156] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. At the same time, other implementation methods can be derived from the above-mentioned embodiments, so that structural and logical replacements and changes can be made without departing from the scope of this disclosure.
[0157] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A method for preparing a composition, characterized in that: The preparation method comprises the following steps: a porous material, a binder, a low shrinkage additive and water are mixed to obtain a mixed slurry, and the mixed slurry is extruded, sheared and baked to obtain a strip and / or rod-shaped product.
2. The preparation method according to claim 1, characterized in that: The raw materials of the composition include: porous material, binder, low shrinkage additive and water; the porous material is selected from: any one or more of zeolite molecular sieve, activated carbon, calcium carbonate, hydrogel or aerogel.
3. The preparation method according to claim 1, characterized in that: The raw materials of the composition include, by mass, 15 to 62 parts of porous material, 15 to 37 parts of binder, 3 to 8 parts of low shrinkage additive, 15 to 40 parts of water and 0.5 to 4 parts of release agent.
4. The preparation method according to claim 2 or 3, characterized in that: The low shrinkage additive is selected from any one or more of polyvinyl acetate, polymethyl methacrylate, polystyrene, thermoplastic polyurethane and polyester.
5. The preparation method according to claim 2 or 3, characterized in that: The binder is selected from any one or more of polyvinyl alcohol, polyurethane, polyurethane acrylate, polyacrylate, epoxy acrylate, polyether acrylate and amino acrylate.
6. The preparation method according to claim 2 or 3, characterized in that: The raw materials of the composition also include: a release agent, and the release agent accounts for 0.5 to 4 parts of the composition.
7. The composition according to claim 6, characterized in that The release agent is selected from any one or more of silicone oil, polyethylene glycol, microcrystalline wax and mica.
8. The preparation method according to claim 1, characterized in that: The length of the product is 3 to 10 mm, and the diameter of the product is 7 to 12 μm.
9. The preparation method according to claim 1 or 8, characterized in that: The sintering temperature of the calcination is 200° C. to 650° C., and the sintering time of the calcination is 0.5 to 5 hours.
10. A loudspeaker sound absorbing material, characterized in that: The loudspeaker sound-absorbing material comprises: a product obtained by the preparation method according to any one of claims 1 to 9 and reinforcing fibers, wherein the composition and the reinforcing fibers are interwoven to form a three-dimensional network structure; The mass ratio of the composition or product to the reinforcing fiber is (30-95):(5-70).
11. The speaker sound absorbing material according to claim 10, characterized in that: The diameter of a single reinforcing fiber is 2 to 30 μm, and the length of a single reinforcing fiber is 3 to 12 mm.
12. A method for manufacturing the loudspeaker sound absorbing material according to any one of claims 10 to 11, characterized in that: The manufacturing method is: Step 1: The composition and / or product and the reinforcing fiber are dispersed and decomposed separately to obtain a first product; Step 2, the first product is dehydrated and paper-formed to obtain a sheet-like second product; Step 3: The second product is subjected to heat pressing to obtain a loudspeaker sound-absorbing material.
13. The manufacturing method according to claim 12, characterized in that: The gram weight of the loudspeaker sound absorbing material is 100 to 800 g / m 2 The thickness of the loudspeaker sound-absorbing material is 0.5 to 2.5 mm.
14. The manufacturing method according to claim 12, characterized in that: In step three, the temperature of the hot pressing is 150° C. to 300° C., and the time of the hot pressing is 3 to 15 minutes.